A broadband three-dimensional dendritic absorbing material and its preparation method and application

A simple preparation method for a three-dimensional dendritic absorbing material addresses the challenges of complex synthesis and narrow bandwidth, achieving high-performance electromagnetic wave absorption with a wide bandwidth and efficient wave attenuation.

CN115666117BActive Publication Date: 2024-12-27ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211291398.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2024-12-27
Estimated Expiration
2042-10-19

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbing materials face challenges with complex synthesis methods, narrow effective absorption bandwidth, and inadequate performance, making them unsuitable for widespread application.

Method used

A simple preparation method for a broadband three-dimensional dendritic absorbing material using 8-hydroxyquinoline, urea, and cobalt nitrate, involving hydrothermal reaction and calcination, results in a unique structure composed of nanorods and nanoparticles, optimizing electromagnetic wave loss mechanisms through spatial order and component adjustment.

Benefits of technology

The material achieves excellent electromagnetic wave absorption with a minimum reflection loss of -51.2dB and a wide effective absorption bandwidth of over 7GHz, demonstrating superior performance in attenuating electromagnetic waves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003897943400000011
    Figure HDA0003897943400000011
  • Figure HDA0003897943400000012
    Figure HDA0003897943400000012
  • Figure HDA0003897943400000013
    Figure HDA0003897943400000013
Patent Text Reader

Abstract

The present invention discloses a broadband three-dimensional dendritic absorbing material and a preparation method and application thereof. The three-dimensional dendritic absorbing material prepared by the present invention uses a Co-based MOF with a dendritic structure as a precursor, and after calcining at different temperatures under nitrogen, a Co / C composite material with a three-dimensional dendritic structure is obtained. Due to the unique structure and multiple loss mechanisms, an effective absorption bandwidth of 7 GHz is obtained under four temperature conditions, and after calcination at 550°C, a reflection loss of ‑51.2 dB is obtained when the thickness is 2.5 mm, and an ultra-wide effective absorption bandwidth of 7.92 GHz is obtained. Therefore, the synergistic effect of the structural design of the material and the loss mechanism is of great significance for optimizing the performance of the absorbing material and broadening the effective absorption bandwidth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a broadband three-dimensional dendritic absorbing material and a preparation method and application thereof. Background Art

[0002] With the vigorous development of the information age, 5G communication technology based on GHz electromagnetic waves has brought ultra-high information transmission efficiency to mobile devices and industrial equipment, triggering the rapid upgrading of intelligent communication and automation industries. However, the widespread application of high-frequency electromagnetic waves with higher electromagnetic energy in 5G technology has also caused the problem of electromagnetic wave pollution. Electromagnetic wave pollution not only interferes with the normal operation of precision instruments and affects the life of instruments and equipment, but also electromagnetic radiation can reduce the body's immunity and may even cause cancer. Therefore, creating efficient electromagnetic wave absorbing materials has become a hot topic of research. At present, many materials have achieved efficient wave absorbing performance, but seeking absorbing materials with wider effective absorption bandwidth has become a bottleneck problem. Therefore, from a scientific point of view, the development of absorbing materials with broadband electromagnetic wave absorption ability is an urgent problem to be solved at present, and it has high research and application value. Generally speaking, constructing a multilayer structure and changing the dielectric constant by changing the heat treatment temperature is conducive to improving the absorbing performance and broadening the effective absorption bandwidth. However, the absorbing materials with multilayer structures prepared at present have cumbersome synthesis steps, are not environmentally friendly and efficient. On the other hand, the final absorbing effect is not excellent, and the effective absorption bandwidth obtained is also small, which is not conducive to better application in real life. Therefore, it is urgent to seek a simple method to obtain efficient and broadband absorbing materials. Therefore, three-dimensional dendritic absorbing materials have good prospects in the field of absorbing materials due to their simple preparation method and ultra-wide effective absorption bandwidth. Summary of the invention

[0003] The purpose of the present invention is to solve the problems of single structure, complicated synthesis method and narrow effective absorption bandwidth of the absorbing material in the prior art, and to provide a preparation and application of broadband three-dimensional dendritic absorbing material. The preparation process of the present invention is simple, the price is low, and large-scale mass production can be achieved. The prepared absorbing material has excellent electromagnetic wave absorption intensity and a wide effective absorption bandwidth.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0005] A broadband three-dimensional dendritic absorbing material is prepared by the following method:

[0006] (1) 8-hydroxyquinoline and urea are uniformly mixed in deionized water A to obtain solution A; cobalt nitrate hexahydrate is dissolved in deionized water B to obtain solution B; solution B is added to solution A (for example, injected with a syringe) under stirring, and the resulting mixed solution is subjected to hydrothermal reaction at 180-220° C. (preferably 200° C.) for 24-48 hours (preferably 24 hours); the resulting reaction solution is post-treated to obtain a precursor of a three-dimensional dendritic structure; the molar ratio of 8-hydroxyquinoline to urea is 1:1-10 (preferably 1:2), the mass ratio of 8-hydroxyquinoline to deionized water A is 1:200-500 (preferably 1:360), and the mass ratio of cobalt nitrate hexahydrate to deionized water B is 1:10-15 (preferably 13.75); the volume ratio of solution A to solution B is 1 to 10:1 (preferably 9:1);

[0007] The above-mentioned deionized water A and deionized water B are both deionized water. Different letters are used here just to distinguish the deionized water added in different stages for the convenience of description.

[0008] (2) placing the precursor of the three-dimensional dendritic structure in step (1) into a tubular furnace, heating it to 450-600°C (preferably 550°C) at a rate of 2°C / min-5°C / min (preferably 5°C / min) under a nitrogen atmosphere, calcining it for 1-3 hours (preferably 2 hours), and then cooling it to room temperature at a rate of 5°C / min-10°C / min (preferably 10°C / min) to obtain the broadband three-dimensional dendritic absorbing material.

[0009] Calcination is to obtain graphitized carbon and magnetic materials, and obtain dielectric\magnetic composite materials.

[0010] The role of post-treatment is to remove impurities.

[0011] Furthermore, in step (1), the solution B can be injected into the solution A by using a syringe. Injection can ensure that the contact area is large enough and that the solution is added quickly, so that the precursor has good morphology uniformity.

[0012] Furthermore, the post-treatment in step (1) is as follows: adding deionized water to the reaction solution and centrifuging (10000 r / min for 10 minutes) to remove the supernatant; performing one or more impurity removal operations on the obtained precipitate: resuspending with anhydrous ethanol, centrifuging (10000 r / min for 10 minutes), and removing the supernatant; and then drying (overnight) to obtain the broadband three-dimensional dendritic absorbing material.

[0013] Preferably, the number of times of impurity removal is 1 to 10 times.

[0014] Preferably, the drying is carried out at 50-90°C, preferably 70°C.

[0015] The present invention particularly recommends the use of the broadband three-dimensional dendritic absorbing material in absorbing electromagnetic waves in the frequency range of 2 to 18 GHz.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention obtains a three-dimensional dendritic absorbing material with preserved morphology by calcining precursors at different temperatures, reveals the electromagnetic wave loss mechanism of the three-dimensional dendritic structure absorbing material, optimizes the process and ultimately achieves the requirements of "wide, light, thin and strong".

[0018] 2. The preparation method of the present invention combines spatial order arrangement and component adjustment to construct a three-dimensional dendritic absorbing material, thereby realizing the superposition of multiple loss mechanisms.

[0019] 3. The three-dimensional dendritic absorbing material prepared by the present invention has a unique structure composed of nanorods and nanoparticles, and the constructed three-dimensional network can quickly attenuate the incident electromagnetic waves into heat energy.

[0020] 4. When an external electric field is applied to the three-dimensional dendritic absorbing material prepared by the present invention, the residual defects and functional groups on its surface will cause polarization relaxation, causing the electromagnetic waves to dissipate.

[0021] 5. The three-dimensional dendritic absorbing material prepared by the present invention has excellent electromagnetic absorption performance. The material has a minimum reflection loss value (RL min ) reached -51.2dB, which can absorb 99.999% of the incident electromagnetic waves. And the effective absorption bandwidth (RL≤-10dB) has been greatly improved (above 7GHz). BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Flow chart for preparing three-dimensional dendritic absorbing materials for Examples 1, 2, and 3.

[0023] Figure 2 This is an X-ray electron diffraction (XRD) pattern of the three-dimensional dendritic absorbing material prepared in Example 1.

[0024] Figure 3 This is a transmission electron microscope (TEM) image of the three-dimensional dendritic absorbing material prepared in Example 1.

[0025] Figure 4 A nitrogen adsorption-desorption (BET) test was performed on the three-dimensional dendritic absorbing material prepared in Example 1.

[0026] Figure 5 This is a hysteresis loop diagram of the three-dimensional dendritic absorbing material prepared in Example 1.

[0027] Figure 6 This is the reflection loss (RL) curve of the three-dimensional dendritic absorbing material prepared in Example 1.

[0028] Figure 7 This is the X-ray electron diffraction (XRD) pattern of the three-dimensional dendritic absorbing material prepared in Example 2.

[0029] Figure 8 This is the reflection loss (RL) curve of the three-dimensional dendritic absorbing material prepared in Example 2.

[0030] Fig. 9 This is the reflection loss (RL) curve of the three-dimensional dendritic absorbing material prepared in Example 3.

[0031] Fig.10 This is the reflection loss (RL) curve of the three-dimensional dendritic absorbing material prepared in Example 4. DETAILED DESCRIPTION

[0032] To facilitate those skilled in the art to understand the present invention, the specific implementation of the present invention is described below in conjunction with the accompanying drawings. It should be understood that the following text is only used to describe one or several specific implementations of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.

[0033] Example 1

[0034] 100 mg (6.89 × 10 -4 mol)8-Hydroxyquinoline (C 9 H 7 NO) and 200 mg (3.33 × 10 -3 moL)urea(CO(NH 2 ) 2 ) and 36 mL of deionized water were mixed and labeled as solution A (the 8-hydroxyquinoline (C 9 H 7 NO) and urea (CO(NH 2 ) 2 ) is 1:2; the deionized water and 8-hydroxyquinoline (C 9 H 7 The mass ratio of NO was 1:360), and magnetic stirring was performed to mix them evenly. 291 mg (1 mol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2O) and 4mL deionized water were mixed and labeled as solution B. While solution A was stirred, solution B was injected with a syringe (the volume ratio of solution A to solution B was 9:1), and then loaded into a 100mL reactor for hydrothermal reaction at 200°C for 24h. After the hydrothermal reaction was completed, it was cooled to room temperature, deionized water was added to the reaction solution and centrifuged (10000r / min for 10 minutes), and the supernatant was removed. The obtained precipitate was resuspended with anhydrous ethanol, centrifuged (10000r / min for 10 minutes), and the supernatant was removed, and then dried at 70°C overnight to obtain the dendritic Co-based MOF precursor. The role of post-treatment is to remove impurities.

[0035] (2) The Co-based MOF precursor obtained in step (1) was placed in a tubular furnace and calcined at 550°C for 2 hours at a heating rate of 5°C / min and a cooling rate of 10°C / min in a nitrogen atmosphere to finally obtain a three-dimensional dendritic absorbing material (Co / C-550) at 550°C.

[0036] The three-dimensional dendritic wave absorbing material prepared in Example 1 and calcined at 550° C. was subjected to an X-ray electron diffraction (XRD) test. The test results are as follows: Figure 2 As shown, the XRD pattern of the three-dimensional dendritic absorbing material prepared by the present invention matches well with the results of crystallographic data simulation, and the material exhibits significant diffraction peaks at 2θ of 44.41°, 51.58°, and 75.98°, corresponding to the characteristic diffraction peaks of Co (111), (200), and (220) crystal planes, which are completely consistent with the standard card of Co (PDF#15-0806), confirming its high purity and high crystallinity.

[0037] The three-dimensional dendritic absorbing material prepared in Example 1 was tested by transmission electron microscopy (TEM). The test results are as follows: Figure 3 As shown in the figure, the material exhibits a three-dimensional dendritic morphology. The three-dimensional dendritic structure is composed of many nanorods, which is conducive to the formation of a three-dimensional network, which will promote the transmission of charges and achieve electromagnetic wave loss under an alternating electromagnetic field. In addition, some metal Co nanoparticles appear on the surface of the nanorods, and gaps are formed between the metal particles. This is conducive to extending the transmission path of electromagnetic waves and increasing the heterogeneous interface between metal particles and carbon skeletons, resulting in interface polarization, thereby improving the absorption performance of the absorbing material.

[0038] The three-dimensional dendritic absorbing material prepared in Example 1 was subjected to nitrogen adsorption-desorption (BET) test. Figure 4 As shown in Figure 2, the material exhibits a typical type IV isotherm, proving the presence of micropores and mesopores. The calculated specific surface area of ​​the material is 118 m 2 g -1The existence of apertures can provide more diffusion pathways for the transmission of electromagnetic waves, showing enhanced wave absorption performance.

[0039] The three-dimensional dendritic wave absorbing material prepared in Example 1 was subjected to a hysteresis loop test. The hysteresis loop curve is shown in FIG. Figure 5 As shown in Figure 2, the material has a typical ferromagnetic hysteresis loop type. The saturation magnetization intensity (M S ) values ​​are 65.9emu / g, and the coercivity is 564Oe. The high saturation magnetization intensity generated may be due to the emergence of more and more metal Co particles, and the Co atom has a high atomic moment of 1.6μB. The Co nanoparticles are spherical, have low anisotropy and nanometer size, and show a high magnetic susceptibility, which easily leads to magnetic moment reversal. Generally speaking, relatively high saturation magnetization intensity and coercivity will contribute to high-frequency resonance, thereby improving the electromagnetic wave absorption performance in high-frequency fields.

[0040] The electromagnetic wave absorbing performance of the three-dimensional dendritic absorbing material prepared in Example 1 was tested. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz is as follows: Figure 6 Generally speaking, an RL value lower than –10dB means that 90% of the electromagnetic waves are absorbed. Figure 5 As shown, the RL of the three-dimensional dendritic absorber min The value is –51.2dB, and the thickness is 2.5mm. The effective absorption bandwidth (RL value < –10dB) is 7.92GHz. The excellent wave absorption performance of the three-dimensional dendritic MOF material can be attributed to its unique three-dimensional layered dendritic structure. The micron-scale dendritic structure assembled by special nanoparticles and nanorods creates a large specific surface area and rich interface polarization and dipole polarization of electromagnetic waves in the material. At the same time, the three-dimensional dendritic structure is conducive to multiple reflections and scattering of electromagnetic waves inside the material, converting electromagnetic waves into other forms of energy such as heat. The carbon nanorods that make up the dendritic structure are intertwined to form a three-dimensional network structure, which enhances the conduction loss of the absorbing material; the presence of uniformly distributed metal nano Co particles also increases more heterogeneous interfaces and promotes the generation of interface polarization; the gaps formed between the metal microspheres, the porous structure of the material itself, and the magnetic / dielectric composite material components greatly improve the broadband impedance matching characteristics of the material, which is conducive to the formation of broadband high-performance absorbing materials. Therefore, the present invention provides a new design idea and technical support for the preparation of lightweight broadband high-performance electromagnetic absorbing materials.

[0041] Example 2

[0042] A preparation and application of a broadband three-dimensional dendritic absorbing material, comprising the following steps (such as Figure 1 ):

[0043] (1) 100 mg (6.89 × 10 -4 mol)8-Hydroxyquinoline (C 9 H 7 NO) and 200 mg (3.33 × 10 -3 moL)urea(CO(NH 2 ) 2 ) and 36 mL of deionized water were mixed and labeled as solution A (the 8-hydroxyquinoline (C 9 H 7 NO) and urea (CO(NH 2 ) 2 ) is 1:2; the deionized water and 8-hydroxyquinoline (C 9 H 7 The mass ratio of NO was 1:360), and magnetic stirring was performed to mix them evenly. 291 mg (1 mol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O) and 4mL deionized water were mixed and labeled as solution B. While solution A was being stirred, solution B was injected with a syringe (the volume ratio of solution A to solution B was 9:1), and then loaded into a 100mL reactor for hydrothermal reaction at 200°C for 24h. After the hydrothermal reaction was completed, it was cooled to room temperature, deionized water was added to the reaction solution and centrifuged (10000r / min for 10 minutes), and the supernatant was removed. The resulting precipitate was resuspended with anhydrous ethanol, centrifuged (10000r / min for 10 minutes), and the supernatant was removed, and then dried at 70°C overnight to obtain the dendritic Co-based MOF precursor. The role of post-treatment is to remove impurities. Among them, Co 2+ / 8-Hydroxyquinoline / urea / H 2 The molar ratio of O is 1:0.7:3.3:2000.

[0044] (2) The Co-based MOF precursor obtained in step (1) was placed in a tubular furnace and calcined at 500°C for 2 hours at a heating rate of 5°C / min and a cooling rate of 10°C / min in a nitrogen atmosphere to finally obtain a three-dimensional dendritic absorbing material (CoO / C-500) at 500°C.

[0045] The three-dimensional dendritic wave absorbing material prepared in Example 2 and calcined at 500° C. was subjected to an X-ray electron diffraction (XRD) test. The test results are as follows: Figure 7As shown, the XRD pattern of the three-dimensional dendritic absorbing material prepared by the present invention matches well with the results of crystallographic data simulation, and the material exhibits significant diffraction peaks at 2θ of 36.48°, 42.38°, 61.43°, 73.65°, and 77.51°, corresponding to the characteristic diffraction peaks of CoO (111), (200), (220), (311), and (222) crystal planes, which are completely consistent with the standard card of CoO (PDF#71-1178), confirming its high purity and high crystallinity.

[0046] The electromagnetic wave absorbing performance of the three-dimensional dendritic absorbing material prepared in Example 2 was tested. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz is as follows: Figure 8 As shown in the figure, the three-dimensional dendritic absorbing material obtained in Example 2 exhibits excellent electromagnetic wave absorption capability when the thickness is 2.0 mm, and the best RL min The value is -33.9dB, and the effective absorption bandwidth is 7.28GHz (10.48-17.76GHz) when the sample thickness is 2.5mm, which still has a wide effective absorption bandwidth. It is well known that changes in the composition of materials have a huge impact on the absorption of electromagnetic waves. Compared with Example 1, the absorbing performance of the three-dimensional dendritic absorbing material synthesized in Example 2 is reduced, which may be due to the difference in the composition of the absorbing material caused by the different calcination temperatures under nitrogen, thereby affecting the dielectric loss of the material.

[0047] Example 3

[0048] A preparation and application of a broadband three-dimensional dendritic absorbing material, comprising the following steps (such as Figure 1 ):

[0049] (1) 100 mg (6.89 × 10 -4 mol)8-Hydroxyquinoline (C 9 H 7 NO) and 200 mg (3.33 × 10 -3 moL)urea(CO(NH 2 ) 2 ) and 36 mL of deionized water were mixed and labeled as solution A (the 8-hydroxyquinoline (C 9 H 7 NO) and urea (CO(NH 2 ) 2 ) is 1:2; the deionized water and 8-hydroxyquinoline (C 9 H 7 The mass ratio of NO was 1:360), and magnetic stirring was performed to mix them evenly. 291 mg (1 mol) of cobalt nitrate hexahydrate (Co(NO 3 )2 6H 2 O) and 4mL deionized water were mixed and labeled as solution B. While solution A was being stirred, solution B was injected with a syringe (the volume ratio of solution A to solution B was 9:1), and then loaded into a 100mL reactor for hydrothermal reaction at 200°C for 24h. After the hydrothermal reaction was completed, it was cooled to room temperature, deionized water was added to the reaction solution and centrifuged (10000r / min for 10 minutes), and the supernatant was removed. The resulting precipitate was resuspended with anhydrous ethanol, centrifuged (10000r / min for 10 minutes), and the supernatant was removed, and then dried at 70°C overnight to obtain the dendritic Co-based MOF precursor. The role of post-treatment is to remove impurities. Among them, Co 2+ / 8-Hydroxyquinoline / urea / H 2 The molar ratio of O is 1:0.7:3.3:2000.

[0050] (2) The Co-based MOF precursor obtained in step (1) was placed in a tubular furnace and calcined at 600°C for 2 hours at a heating rate of 5°C / min and a cooling rate of 10°C / min in a nitrogen atmosphere to finally obtain a three-dimensional dendritic absorbing material (Co / C-600) at 600°C.

[0051] The three-dimensional dendritic absorbing material prepared in Example 3 was tested for electromagnetic wave absorbing performance. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz is as follows: Fig. 9 As shown. For the three-dimensional dendritic absorbing material obtained in Example 3, the corresponding optimal reflection loss value is -25.4dB, and the effective absorption bandwidth when the thickness is 2.5mm is 7.84GHz (10.08-17.92GHz). It still has a very wide effective absorption bandwidth, and the decline in wave absorption performance may be due to the fact that the calcination temperature is too high and the dendritic morphology changes slightly. The wave absorption mechanism of the three-dimensional dendritic absorbing material is as follows: First, the special multilayer stacking structure is conducive to the construction of three-dimensional channels and the transmission and transition of carriers. Second, the three-dimensional dendritic structure is conducive to the formation of more heterogeneous interfaces, increases the electron aggregation at the interface, and prolongs the transmission path of electromagnetic waves inside the material. Third, the formation of a porous structure is conducive to optimizing the impedance matching between the material surface and the free space, and enhancing the electromagnetic wave absorption capacity. Fourth, the formation of gaps between the metal microspheres, the porous structure of the material itself, and the magnetic / dielectric composite material components greatly improve the broadband impedance matching characteristics of the material, which is conducive to the formation of broadband high-performance absorbing materials. In summary, different calcination temperatures will cause changes in the composition and morphology of the absorbing material, and therefore the electromagnetic wave absorption performance will also change accordingly.

[0052] Example 4

[0053] 100 mg (6.89×10-4 mol) 8-hydroxyquinoline (C 9 H 7 NO) and 200 mg (3.33 × 10-3 mol) urea (CO(NH 2 ) 2 ) and 36 mL of deionized water were mixed and labeled as solution A (the 8-hydroxyquinoline (C 9 H 7 NO) and urea (CO(NH 2 ) 2 ) is 1:2; the deionized water and 8-hydroxyquinoline (C 9 H 7 The mass ratio of NO was 1:360), and magnetic stirring was performed to mix them evenly. 291 mg (1 mol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O) and 4mL deionized water were mixed and labeled as solution B. While solution A was stirred, solution B was injected with a syringe (the volume ratio of solution A to solution B was 9:1), and then loaded into a 100mL reactor for hydrothermal reaction at 200°C for 24h. After the hydrothermal reaction was completed, it was cooled to room temperature, deionized water was added to the reaction solution and centrifuged (10000r / min for 10 minutes), and the supernatant was removed. The obtained precipitate was resuspended with anhydrous ethanol, centrifuged (10000r / min for 10 minutes), and the supernatant was removed, and then dried at 70°C overnight to obtain the dendritic Co-based MOF precursor. The role of post-treatment is to remove impurities.

[0054] (2) The Co-based MOF precursor obtained in step (1) is directly tested for its microwave absorption performance without calcination.

[0055] The three-dimensional dendritic precursor prepared in Example 4 was tested for electromagnetic wave absorption performance. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz is as follows: Fig.10 As shown. For the three-dimensional dendritic absorbing material obtained in Example 4, the corresponding optimal reflection loss value is -7.64dB, and the thickness is 3mm. The results show that it has a very narrow effective absorption bandwidth and the absorbing performance is significantly reduced, mainly due to the poor conductivity and lack of magnetism, so the absorption effect of electromagnetic waves is very poor.

[0056] The above is a detailed description of the implementation mode of the present invention in conjunction with the embodiments, which does not limit the present invention in any form. For those skilled in the art, after knowing the contents recorded in the present invention, they can make several improvements and substitutions without departing from the principle of the present invention, and these equivalent improvements and substitutions should be included in the scope of protection of the claims of the present invention.

Claims

1. A broadband three-dimensional dendritic absorbing material, characterized in that The broadband three-dimensional dendritic absorbing material is prepared as follows: (1) 8-hydroxyquinoline and urea are uniformly mixed in deionized water A to obtain solution A; cobalt nitrate hexahydrate is dissolved in deionized water B to obtain solution B; solution B is added to solution A under stirring, and the resulting mixed solution is subjected to hydrothermal reaction at 180-220° C. for 24-48 hours, and the resulting reaction solution is post-treated to obtain a precursor of a three-dimensional dendritic structure; the molar ratio of 8-hydroxyquinoline to urea is 1:1-10, the mass ratio of 8-hydroxyquinoline to deionized water A is 1:200-500, and the mass ratio of cobalt nitrate hexahydrate to deionized water B is 1:10-15; the volume ratio of solution A to solution B is 1 to 10:1; The post-treatment is as follows: adding deionized water to the reaction solution, centrifuging, and removing the supernatant; performing 1 to 10 impurity removal operations on the obtained precipitate: resuspending with anhydrous ethanol, centrifuging, and removing the supernatant; drying at 50 to 90° C. to obtain the precursor of the three-dimensional dendritic structure; (2) The precursor of the three-dimensional dendritic structure in step (1) is placed in a tubular furnace, heated to 550°C at a rate of 2°C / min-5°C / min under a nitrogen atmosphere and calcined for 2 hours, and then cooled to room temperature at a rate of 5°C / min-10°C / min to obtain the broadband three-dimensional dendritic absorbing material.

2. The broadband three-dimensional dendritic absorbing material according to claim 1, characterized in that: In step (1), the solution B is injected into the solution A using a syringe.

3. The broadband three-dimensional dendritic absorbing material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 200° C. and the time is 24 h.

4. The broadband three-dimensional dendritic absorbing material according to claim 1, characterized in that: The molar ratio of 8-hydroxyquinoline to urea in step (1) is 1:

2.

5. The broadband three-dimensional dendritic absorbing material according to claim 1, characterized in that: The volume ratio of solution A to solution B in step (1) is 9:

1.

6. Use of the broadband three-dimensional dendritic absorbing material as claimed in claim 1 in absorbing electromagnetic waves in the frequency range of 2 to 18 GHz.